Anti-Cancer Effects of CKD-581, a Potent Histone Deacetylase Inhibitor against Diffuse Large B-Cell Lymphoma - Kim, Soo Jin (Int J Mol Sci, 2020)
Double-hit lymphoma (DHL) and double-expressor lymphoma (DEL) are aggressive forms of lymphoma that require better treatments to improve patient outcomes. CKD-581 is a new histone deacetylase (HDAC) inhibitor that exhibited a better safety profile in clinical trials compared to other HDAC inhibitors. Here, we demonstrate that CKD-581 inhibited the class I–II HDAC family via histone H3 and tubulin acetylation. CKD-581 treatment also up-regulated the phosphorylation of histone H2AX (γH2AX, DNA double-strand break marker), and reduced levels of MYC and anti-apoptotic proteins such as BCL-2, BCL-6, BCL-(X)L, and MCL-1 in DH/DE-diffuse large B cell lymphoma (DLBCL) cell lines. Ultimately, CKD-581 also induced apoptosis via poly(ADP ribose) polymerase 1 (PARP1) cleavage. In a DLBCL SCID mouse xenograft model, CKD-581 exhibited anti-cancer effects comparable with those of rituximab (CD20 mAb). Our findings suggest that CKD-581 could be a good candidate for the treatment of DLBCL.